Basics of olympiad inequalities by Riasat S.

By Riasat S.

Show description

Read or Download Basics of olympiad inequalities PDF

Similar elementary books

Notes on Rubik's Magic Cube

Notes on Rubik's 'Magic dice'

Beginner's Basque

This identify encompasses a publication and a pair of audio CDs. Basque is the language spoken by means of the Basque those that dwell within the Pyrenees in North important Spain and the adjacent sector of south west France. it's also spoken through many immigrant groups world wide together with the USA, Venezuela, Argentina, Mexico and Colombia.

Elementary Algebra

Trouble-free Algebra is a piece textual content that covers the conventional themes studied in a latest uncomplicated algebra direction. it really is meant for college students who (1) haven't any publicity to basic algebra, (2) have formerly had an uncongenial adventure with uncomplicated algebra, or (3) have to evaluation algebraic thoughts and strategies.

Extra resources for Basics of olympiad inequalities

Sample text

Deduce a proof of Nesbitt’s inequality from Chebyshev’s inequality. 4. Let a1 ≥ a2 ≥ · · · ≥ an and b1 ≤ b2 ≤ · · · ≤ bn be positive. Prove that n i=1 ai a1 + a2 + · · · + an n(a1 + a2 + · · · + an ) √ ≥ . ≥ n bi b1 + b2 + · · · + bn b1 b2 . . 5. Let a ≥ c ≥ 0 and b ≥ d ≥ 0. Prove that (a + b + c + d)2 ≥ 8(ad + bc). 6. (Radu Titiu) Let a, b, c > 0 such that a2 + b2 + c2 ≥ 3. Show that a2 b2 c2 3 + + ≥ . 3. 7. Let a, b, c > 0 such that abc = 1. Prove that 9 ≤ 2 cyc 1 · + b) c2 (a ab ≤ 3 cyc cyc ab .

Similarly one might also assume a + b + c = 1. The reader is requested to find out how it works. 6 Homogenization This is the opposite of Normalization. It is often useful to substitute a = x/y, b = y/z, c = z/x, when the condition abc = 1 is given. Similarly when a + b + c = 1 we can substitute a = x/x + y + z, b = y/x + y + z, c = z/x + y + z to homogenize the inequality. 1 in the following form: a b c a+b+c + + ≥ √ . 3 b c a abc On the other hand, if we substitute a = x/y, b = y/z, c = z/x the inequality becomes, zx xy yz x y z + 2 + 2 ≥ + + , 2 y z x y z x which clearly looks easier to deal with (Hint: Rearrangement).

B+c bn + bn−1 c c+a cyc cyc cyc 26 CHAPTER 3. 1 Schur’s Inequality Let a, b, c be positive real numbers, and n be positive. Then the following inequality holds: an (a − b)(a − c) + bn (b − c)(b − a) + cn (c − a)(c − b) ≥ 0, with equality if and only if a = b = c or a = b, c = 0 and permutations. The above inequality is known as Schur’s inequality, after Issai Schur. Proof. Since the inequality is symmetric in a, b, c WLOG we may assume that a ≥ b ≥ c. Then the inequality is equivalent to (a − b)(an (a − c) − bn (b − c)) + cn (a − c)(b − c) ≥ 0, which is obviously true.

Download PDF sample

Rated 4.69 of 5 – based on 27 votes